The Determinants of Performance in Biathlon World Cup Sprint and Individual Competitions - Björklund, Glenn; Laaksonen, Marko S. (Frontiers in Sports and Active Living, 2022)
Purpose: The aim of the present study was to determine the association of skiing speed (SS), range time (RT) and number of missed targets (MT) to rank in sprint and individual biathlon competitions. Methods: Data were collected from the International Biathlon Union’s database for 17 seasons (2002/2003 – 2018/2019). Furthermore, the biathletes were divided into three rank groups (G3, rank 1-3; G10, rank 4-10 and G20, rank 11-20). Multinominal regression was used to detect odds ratios associated to group rank for both sexes, separately. Results: MT was the only variable that constantly related to G3 (OR 1.90 – 6.35, all p < 0.001) for both women and men. SS was associated with G3 in the last lap in the sprint for both sexes (OR 0.46 – 0.66, all p < 0.001) and RT for standing shooting (OR 1.04 – 1.14, all p < 0.05). Conclusion: These results show that shooting is fundamental factor for performance in both competitions, but that skiing speed is increasingly important for the last lap in the sprint for both sexes. Further, a fast RT in the standing shooting for women in individual and for men in the sprint seems important for improving final rank.